Exclusive Breastfeeding and The Importance of Breastfeeding Self-Efficacy in Working Women at Korpri Primary Health Care - Budiarti, Indah; Suja, Monica Dara Delia (Fakultas Ilmu Kesehatan, 2024)
Exclusive breastfeeding in the first 6 months of life can reduce 13 of toddler deaths and is one of the dimension strategies to ameliorate the nutritive status and survival of toddlers. In 2020 exclusive breastfeeding until the baby is 6 months old in Indonesia is still low, videlicet only15.3. Failure to give exclusive breastfeeding is frequently a problem for suckling maters. This problem can be caused by several factors, similar as knowledge, social support, tone- confidence to breastfeed, or suckling tone- efficacity( BSE). This study aims to determine the relationship between breastfeeding tone- efficacity( BSE) and the success of furnishing exclusive breastfeeding to working maters in the Korpri Health Center work area, Bandar Lampung City. This exploration uses across-sectional exploration design. The repliers in this study were postpartum maters in the Korpri Health Center working area in Bandar Lampung City. Samples were named using intentional slice ways and establishing addition and rejection criteria. The sample in this study was 50 repliers. The exploration results show that there's a significant relationship between breastfeeding tone- efficacity and exclusive breastfeeding for working maters. suckling tone- efficacity is a factor that must be considered by the government to increase exclusive breastfeeding content.